Perbaikan Kualitas Hidup pada Pasien Solitary Fibrous Tumor Mediastinum: Perspektif Kemoterapi Paliatif: [Improvement of Quality of Life in Mediastinal Solitary Fibrous Tumor: Paliative Chemoteraphy Perspective] - Aryo Dirgantara Putra; Winarinani Koesoemoprodjo (Jurnal Respirasi, 2019)
Background: Mediastinal solitary fibrous tumor (SFT) is a rare spindle cell neoplasm. Approximately 1 to 8% of these intrathoracic tumors have been reported to occur in the mediastinum. The chief complaints of mediastinal SFT are cough, shortness of breath or chest pain, or may occur as asymptomatic incidental mass. The treatment of choice for SFT is extensive surgical resection. However, when the tumor cannot be removed surgically or when metastases occur, chemotherapy and or radiotherapy can be proposed as palliative treatments. Case: A 19-year-old man with chief complaint of left chest pain and referred to his left back. The complaint is accompanied by cough without sputum and hoarseness. In thoracic CT scan with contrast, we found giant cystic mass suspect malignancy around 17x12x18 cm in left hemithorax, a minimal pericardial effusion, and left pleural effusion. There were positive tumor cell cytoplasm results in vimentin, negative tumor cell cytoplasm in CK, positive tumor cell membrane in CD99, cytoplasm of focal positive tumor cells in EMA, and negative tumor cells in CD34 which supported a solitary fibrous tumor in the immunohistochemical staining analysis. Doxorubicin-Ifosfamide regimen was the choice of chemotherapy palliative treatment in the case report. In the CT scan evaluation of thorax with contrast, we found stable disease (RECIST criteria) with improve quality of life (QOL) according to EQ-5D-3L, 11111 indicated no problems in 5 dimensions, such as mobility, self-care, usual activities, pain or discomfort, and anxiety or depression. Conclusion: Mediastinal SFT is a rare spindle cell neoplasm, and the diagnosis requires pathological and immunohistochemical staining analysis. Doxorubicin-Ifosfamide regimen can be proposed as a palliative chemotherapy regimen, which has been shown to improve QOL patients in Mediastinal SFT. EQ-5D is a simple tool that can be used to measure QOL such as mobility, self-care, usual activities, pain or discomfort, and anxiety or depression.